Revisiting perspectives on George Homans: correcting misconceptions. Issue 1 (8th January 2018) - Muldoon, Jeff; Liguori, Eric W.; Bendickson, Josh; Bauman, Antonina
Abstract : Purpose: This paper aims to correct some misconceptions about George Homans. Specifically, it clarifies the relationship between Homans and Malinowski, explains why Homans is rightfully considered the father of social exchange, shows Homans' perspective on altruism and self-interest and analyses Homans' place in management's complex history. Design/methodology/approach: This is a conceptual paper which synthesizes both primary and secondary sources on Homans, social exchange theory (SET), Malinowski and other Homans' contemporaries and theories, which, in aggregate, help dispel some common misconceptions in the literature today. Findings: This paper disperses several common misconceptions about Homans and his work. First, the findings show that beliefs that Homans was unaware of Malinowski are not justified, as Homans was not only aware of Malinowski but also significantly influenced by Malinowski's work. Second, this manuscript clarifies that while Homans, for specific reasons, focussed on self-interest, his work accounted for altruism. Lastly, this paper also further cements Homans' place in history as the father of social exchange. Originality/value: Recent misconceptions have emerged in the literature calling to question not only Homans' legitimacy as the father of social exchange but also some of his views on the theory itself. By clarifying these misconceptions, this paper enables scholars from a variety of management fields to better understand historical foundations of SET and its impact on current research.